Maternal bisphenol a exposure impacts the fetal heart transcriptome. - Kalyan C Chapalamadugu; Catherine A Vandevoort; Matthew L Settles; Barrie D Robison; Gordon K Murdoch (PLoS ONE)
Conditions during fetal development influence health and disease in adulthood, especially during critical windows of organogenesis. Fetal exposure to the endocrine disrupting chemical, bisphenol A (BPA) affects the development of multiple organ systems in rodents and monkeys. However, effects of BPA exposure on cardiac development have not been assessed. With evidence that maternal BPA is transplacentally delivered to the developing fetus, it becomes imperative to examine the physiological consequences of gestational exposure during primate development. Herein, we evaluate the effects of daily, oral BPA exposure of pregnant rhesus monkeys (Macaca mulatta) on the fetal heart transcriptome. Pregnant monkeys were given daily oral doses (400 µg/kg body weight) of BPA during early (50-100 ± 2 days post conception, dpc) or late (100 ± 2 dpc--term), gestation. At the end of treatment, fetal heart tissues were collected and chamber specific transcriptome expression was assessed using genome-wide microarray. Quantitative real-time PCR was conducted on select genes and ventricular tissue glycogen content was quantified. Our results show that BPA exposure alters transcription of genes that are recognized for their role in cardiac pathophysiologies. Importantly, myosin heavy chain, cardiac isoform alpha (Myh6) was down-regulated in the left ventricle, and 'A Disintegrin and Metalloprotease 12', long isoform (Adam12-l) was up-regulated in both ventricles, and the right atrium of the heart in BPA exposed fetuses. BPA induced alteration of these genes supports the hypothesis that exposure to BPA during fetal development may impact cardiovascular fitness. Our results intensify concerns about the role of BPA in the genesis of human metabolic and cardiovascular diseases.